A Case Study On Digital Divide And Access To Information Communication Technologies (Icts) In Pulau Tuba, Langkawi, Malaysia - et. al., Mohamad Yusof Darus, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Digital divide is referring to the gap between demographics and regions that have access to modern information and communications technology, and those that don't or have restricted access such as internet. The digital divide continues an important public policy debate that encompasses social, economic and political issues. This research focuses on to identify internet accessibility factors at Pulau Tuba Langkawi. In this research study, we focus on surveying internet accessibility and conducting an interview using quantitative study. Internet accessibility is conducted using OpenSignal application. OpenSignal is application to build a network coverage map of cellular network. For second method, quantitative survey was conducted by interviewing and questionnaire, with the sample size of the survey is 30. From this research, the results show only two spots which has good internet coverage which are near a primary school which are government owned premises. On the other hand, the area along the beach has moderate to bad internet coverage and certain place such as Lubuk Chempedak has very limited internet coverage. From quantitative survey, majority of population has average competent level of knowledge and skills to use the internet application such as email, online banking etc. Furthermore, the results show that majority of population strongly agreed that internet has the potential to increase their income and market their local product to bigger market. However, majority of them unable to use the internet and benefits from it due to poor internet accessibility. Therefore, more IT educational program and training should be given, and the government and local authority must play its part to improve the internet infrastructure so that the population did not continue being left out from the development of digital economy.